Disaster Management in the Palm Oil Industry Using Industrial Engineering Methods with Monte Carlo Simulation and Survival Analysis - Suksmanatyo; Wahyudi, Brian Fitri; Hidayat, Muhammad Taufiq; Suheriyanto; Yulianto; Aulady, M. Ferdaus Noor (Journal of Advances in Information and Industrial Technology, 2025)
The palm oil industry is a strategic sector that plays a significant role in foreign exchange earnings and national employment, but is highly vulnerable to disaster risks, both from natural (floods, fires) and technical (machine breakdowns, supply chain disruptions) factors. This study develops an industrial engineering-based disaster management framework by integrating Monte Carlo Simulation to estimate economic losses and Survival Analysis (Kaplan–Meier and Log-Rank Test) to assess the operational resilience of palm oil mills. The simulation results show an average annual loss of IDR 3.87 billion, with a 95% VaR of IDR 8.97 billion and a 95% CVaR of IDR 11.25 billion. Factors such as preventive maintenance, the location of the mill in a flood-prone area, and the availability of backup power sources significantly influence post-disaster recovery time. This study provides a quantitative basis for the allocation of financial risk reserves and strategic recommendations to improve the operational resilience of the palm oil industry to disaster uncertainty.